2018
DOI: 10.3390/resources7020034
|View full text |Cite
|
Sign up to set email alerts
|

The Local Value Chain of Hunted Red Deer Meat: A Scenario Analysis Based on a Northern Italian Case Study

Abstract: Although in recent decades, meat from hunted wild ungulates has shown interesting results in terms of market opportunities, the scientific literature is still lacking in economic studies concerning the estimation of the meat's value for involved stakeholders. We present an analysis of the evolution of price in the local red deer meat supply chain. This analysis has been conducted through a survey based on in-depth interviews with the stakeholders involved in an Italian local supply chain. Findings derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Finally, we asked if the participants perceived hunting as "traditional" and as a "food production activity that provides food that is suitable for human consumption". We add this question because even if hunting is a traditional method used to procure food, hunters do not need to be food professionals, which could generate a lack of trust between consumers and producers (Gaviglio, Marescotti, & Demartini, 2018). The "I don't know" option was used also in this scale, and the same considerations as discussed in the previous paragraph were included for the case of wild game meat evaluations.…”
Section: Scale Used For the Measurement Of Attitudes Toward Huntingmentioning
confidence: 99%
“…Finally, we asked if the participants perceived hunting as "traditional" and as a "food production activity that provides food that is suitable for human consumption". We add this question because even if hunting is a traditional method used to procure food, hunters do not need to be food professionals, which could generate a lack of trust between consumers and producers (Gaviglio, Marescotti, & Demartini, 2018). The "I don't know" option was used also in this scale, and the same considerations as discussed in the previous paragraph were included for the case of wild game meat evaluations.…”
Section: Scale Used For the Measurement Of Attitudes Toward Huntingmentioning
confidence: 99%
“…Only few studies take into consideration the hunters as primary producers of the HWGM supply chain. For instance, Gaviglio et al [ 71 , 72 ] estimated the economic value, the quality and the quantity of the HWGM suitable for the sale by interviewing a sample of Italian hunters and found that the meat of a relevant part of the sample lacks the hygienic and quality standards required for trade. Furthermore, Caro et al [ 73 ] explored the hunters’ perceptions regarding the positive and negative aspects associated with hunting practices and found that Spanish hunters felt misunderstood and even attacked by society.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of clarity on commercial standards implies very high transaction costs along the supply chain, preventing Italian hunters to consider themselves as producers and to consider wild ungulates meat as a food product that can enter the general market [ 71 ]. As a consequence, the Italian hunting sector continues to be a very ‘private’ affair with hunted meat consumed by the hunters and their acquaintances [ 71 , 72 , 74 ]. Nonetheless, the few data collected on Italian production of HWGM in the last decade highlights that hunted meat might represent an attractive alternative to farmed meats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of placing wild game meat on the market according to Reg. (EC) n. 853/2004, which considers the hunter a primary producer, represents an added value for the sustainable use of ungulates as resources in rural areas with a potential economic impact on the local economy (Gaviglio et al , 2017; Gaviglio et al , 2018). In recent decades, ungulates have shown a remarkable demographic increase in Italy, especially for red deer (Ramanzin et al , 2010) and wild boar, which is often considered more a damage than a resource (Ferri, 1998).…”
Section: Introductionmentioning
confidence: 99%